Strategic Planning for Non-Profit Organization: Ensuring Operational Sustainability and Expanding Social Impact at Widya Erti Indonesia - Murti, I Made Wiranatha Krisna; Lantu, Donald Crestofel (Yayasan Sinergi Kawula Muda, 2025)
This study focuses on Widya Erti Indonesia (WEI), a non-profit organization working in the field of sustainable rural development. The research aims to analyze the internal and external factors influencing WEI’s ability to maintain program effectiveness, scale its operations, and respond to the evolving development landscape in Indonesia. The central issue addressed in this research is how WEI can strategically strengthen its position, given the limitations in internal resources and the complexity of external demands. These issues are particularly relevant as development funding structures shift, climate risks grow, and expectations for nonprofit accountability increase. The objectives of the study are threefold: (1) to identify WEI’s internal strengths and weaknesses, (2) to examine external opportunities and threats and (3) to formulate strategic planning to enhance to ensure its long-term sustainability and increase its impact on rural communities. This qualitative descriptive research employs SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to assess internal and external organizational conditions. It is complemented by the STEEPLE framework (Social, Technological, Economic, Environmental, Political, Legal, and Ethical factors) to provide a broader analysis of the external macro-environment affecting WEI’s strategic positioning. Data were collected through focus group discussions (FGDs), key informant interviews, and literature review of donor trends, regulatory changes, and industry reports. To address these challenges, the study recommends three priorities: strengthening governance and systems, diversifying funding, and scaling up community-based approaches. Through partnerships and improved accountability, WEI can achieve greater sustainability and social impact in the next five years.